Excellent catalysis of MoO3 on the hydrogen sorption of MgH2. (8th November 2019) - Dan, Liang; Hu, Long; Wang, Hui; Zhu, Min
Abstract: To improve the hydrogen sorption kinetics of MgH2, the MoO3 nanobelts were added into MgH2 by mechanical milling, leading to fine distribution of MoO3 in the MgH2 matrix. Compared to uncatalyzed MgH2, the hydriding and dehydriding rates of MoO3 -catalyzed MgH2 were significantly improved. The MgH2 doped with 2 mol% MoO3 exhibited fast dehydrogenation without activation, and the initial dehydrogenation amount of 5 wt% could be reached within 900 s at 300 °C. The dehydrogenation apparent activation energy is decreased down to 114.7 kJ/mol. The excellent catalytic effect of MoO3 originates from its specific role as fast hydrogen diffusion pathways. In the hydrogenation process, the MoO3 transformed to MoO2, resulting in the fading of catalytic activity. Highlights: The MoO3 nanobelts were finely dispersed in the MgH2 by mechanical milling. The MoO3 has excellent catalytic effect on the dehydrogenation of MgH2 . The excellent catalytic activity of MoO3 is related to its multi-valence and its specific role as hydrogen diffusion pathway.